2023
DOI: 10.1111/add.16119
|View full text |Cite
|
Sign up to set email alerts
|

The association of lowered alcohol prices with birth outcomes and abortions: A population‐based natural experiment

Abstract: Background and Aims: Alcohol use during pregnancy remains an important risk factor for adverse birth outcomes, but little is known regarding how alcohol prices affect pregnancy outcomes on the population level. We assess the associations between decreased alcohol prices with birth outcomes and abortions.Design: Using national registers, we used interrupted time-series modelling to compare outcomes of pregnancies conceived before and after a tax cut, resulting in 33% mean decrease of off-premise alcohol prices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although NTDs are not common among FAS patients, they occur more frequently in this group of patients than in the general population. The induction of NTDs in humans and other vertebrate experimental models by EtOH exposure during embryogenesis, is likely due to the reduction in RA levels, with the lower incidence of severe NTD forms among FAS patients probably the result of embryonic lethality ( Windham et al, 1997 ; Andersen et al, 2012 ; Luukkonen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although NTDs are not common among FAS patients, they occur more frequently in this group of patients than in the general population. The induction of NTDs in humans and other vertebrate experimental models by EtOH exposure during embryogenesis, is likely due to the reduction in RA levels, with the lower incidence of severe NTD forms among FAS patients probably the result of embryonic lethality ( Windham et al, 1997 ; Andersen et al, 2012 ; Luukkonen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It finds that increased adverse birth outcomes followed a decrease in alcohol prices, although this increase was not sustained. While alcohol pricing policy is clearly not the single solution that will eliminate harms related to pregnant people’s alcohol consumption, the research [9] provides additional evidence to support the pattern of findings from the small body of literature examining general population alcohol policies and birth outcomes. In the United States the focus has been on minimum legal drinking age policies; the research examining the relationship has consistently found improved birth outcomes associated with higher minimum legal drinking ages [10, 11].…”
mentioning
confidence: 85%
“…Luukkonen et al .’s paper is an excellent example of a well‐designed study that helps with the third approach. This paper examines the relationship between a change in alcohol prices and birth outcomes in Finland [9]. It finds that increased adverse birth outcomes followed a decrease in alcohol prices, although this increase was not sustained.…”
mentioning
confidence: 99%